Design and characterization of uplink antenna for nano-satellite applications - Kwan, Felicia Shu Bing. (2012)
This is a final year project report that states the process of the implementation of a 6 sided hexagonal loop antenna for a 440 MHz nano-satellite application. Hexagonal loop antenna is chosen for this project as it exhibits 10% more gain as compared to a dipole antenna and it also has higher noise immunity as compared to other antennas.